Pengaruh Penggunaan Model Problem Based Learning (PBL) Terhadap Hasil Belajar Penjumlahan dan Pengurangan Pecahan di Kelas V SD Gugus IV Padang Utara Kota Padang - Putri, Vipin Cenya; Dalais, Mursal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This research is backed by the learning of addition and fractional reduction that is still dominated by teachers and is less associated with problems related to the real world of students. The purpose of the research is to know the influence of Problem Based Learning model on the result of the addition and fractional reduction in class V Elementary School gugus IV North Padang, Padang City on 2018/2019 school year.The type of this research is Quasi-experimental design. The population in this study is all students of class V elementary school gugus IV North Padang, consisting of 11 schools. The results by Purposive Sampling technique are Elementary School 05 Air Tawar Barat and Elementary School 09 Air Tawar Barat. Elementary School 05 Air Tawar Barat as a control class and SDN 09 Air Tawar Barat as an experimental class. The research instrument is a essay-written test. The data analysis technique used is t-test.Based on the results of the research gained the average postest value of addition and fractional reduction by using the Problem Based Learning model in the Experiment Group is 85,16 and control groups using learning Conventional is 78, 36. This means of the group's precedence higher than the control groups. From the result of calculation of t-test obtained tcount 2.075 while the ttable with a significant status of 0.05 and dk = 62 is 1,998. Means tcount > ttable so H1 is accepted. Thus, there is a significant influence of Problem  Based Learning model for the learning outcomes of the addition and fractional reduction in class V SD gugus IV North Padang, Padang City.